Two new species of Austrophthiracarus (Acari: Oribatida: Phthiracaridae) from New Zealand - Liu, Dong; Zhang, Zhi-Qiang (Zootaxa, 2013)
The genus Austrophthiracarus (Acari: Oribatida: Phthiracaridae) was represented in New Zealand by four species prior to this work. In this paper, two new species of Austrophthiracarus are described from the South Island, New Zealand: Aus-trophthiracarus cronadun sp. nov. collected near Cronadun, Buller and Austrophthiracarus tawhai sp. nov. from Catlins State Forest, Otago. A key to all known species of Austrophthiracarus in New Zealand is provided.